2020
DOI: 10.2196/16367
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use Among Young Adults With Connective Tissue Disorders: Cross-Sectional Pilot Study

Abstract: Background Young people with genetic conditions often face challenges coping with their health condition. It can be difficult for them to meet someone with a similar condition, which is important for reinforcement of chronic illness management recommendations. Social media is used by 97% of young people in the United States and may provide those with these disorders a space for emotional expression and support. However, there is a scarcity of literature related to the use of social media among adol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…One Italian study that studied patients with 4 conditions, including IBD and T1D, found that 98% expressed a need to share their medical condition on social media [ 14 ]. However, another study of patients with connective tissue disorders noted only 17% revealed their condition on social media [ 15 ]. These studies can be used to put the disclosure rate of young adults with IBD and T1D in context.…”
Section: Discussionmentioning
confidence: 99%
“…One Italian study that studied patients with 4 conditions, including IBD and T1D, found that 98% expressed a need to share their medical condition on social media [ 14 ]. However, another study of patients with connective tissue disorders noted only 17% revealed their condition on social media [ 15 ]. These studies can be used to put the disclosure rate of young adults with IBD and T1D in context.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, social media provides easy access to a forum where individuals can turn for social support. Online social networking allows for communities, such as the LGBTQ (lesbian, gay, bisexual, transgender, and queer or questioning) community or communities of children with chronic health conditions, to meet and interact with each other (Kelleher et al, 2020; Sherrell & Johnson, 2021).…”
Section: Rise In Social Media Usementioning
confidence: 99%
“…За рубежом термином «дисплазия соединительной ткани» называют гетерогенную группу наследственных заболеваний (таких как синдром Марфана, синдром Элерса -Данлоса) [13]. Другие авторы термином "undifferentiated (mixed) connective tissue dysplasia" (недифференцированная дисплазия соединительной ткани) называют группу аутоиммунных заболеваний, включая системную красную волчанку, системный склероз, идиопатические воспалительные миопатии, синдром Шегрена и ревматоидный артрит, в связи с чем может быть некоторая путаница при переводе (в российской классификации термином «недифференцированная дисплазия соединительной ткани» называют несиндромные мультифакториальные дисплазии соединительной ткани) [14].…”
Section: терминологияunclassified